Reasons why older adults play sport: A systematic review - Brad J. Stenner; Jonathan D. Buckley; Amber D. Mosewich (Journal of Sport and Health Science, 2020)
Background: Despite the known contribution of sport to health and well-being, sport participation declines in older age. However, for some people, sport continues to play an important role in older age and may contribute to improved health and well-being in older years. Although the health-related benefits of participating in sport are commonly reported, the reasons why some older adults continue to play sport are not well understood. This systematic review aimed to (1) identify studies from the literature that evaluated the reasons why older adults (aged 55 years and older) participate in sport and (2) synthesize and discuss the reasons for their participation reported in the literature. Methods: Searches of the electronic databases Embase, Medline, PsycInfo, PubMed, and SPORTDiscus were performed. Studies were included that evaluated reasons for sport participation in adults aged 55 years and older because this is the age at which sport participation has been reported to begin declining. The studies included in this review used qualitative, quantitative, or mixed methods designs, were peer reviewed, and were published in the English language before the search date (20 January 2019). Results: A total of 1732 studies were identified. After exclusions, 30 studies were included in the review (16 qualitative, 10 quantitative, and 4 mixed methods). The review presents several features and findings from the studies, including a description and systematization of the reasons for participating in sport and the main reasons that participants gave for participating in sport (maintaining health, feeling and being part of a community, and taking advantage of opportunities to develop relationships). Other reasons included competing and attaining a feeling of achievement, taking advantage of opportunities for travel, and being part of a team. Sport was identified as contributing to the overall experience of successful ageing. There were few comparative differences for participating in sport, and there were only small differences between genders for the reasons given for participation. Generally, the quality of the studies was good; however, mixed methods studies lacked appropriate data analysis procedures. Conclusion: Older adults play sport for a range of health-related and social reasons that can contribute to the experience of successful ageing. Strategies to increase sport participation by older adults should focus on promoting these aspects.